Management Model of Inclusive Education in Indonesia: A Comprehensive Review of Islamic Education Perspectives - Fahrurrosi, Lingga; Marzuki, Nurmila Binti; Husni, Muhmmad; Kamilia, Zahrotal (STAI Publisistik Thawalib Jakarta, 2025)
Inclusive education in Indonesia has gained increasing attention, yet the integration of Islamic education principles into its management remains underexplored. Despite strong legal foundations, including Law Number 20 of 2003 on the National Education System and Law Number 8 of 2016 on Persons with Disabilities, the practical implementation of inclusive education faces significant challenges. The research gap lies in the limited understanding of how Islamic ethical and educational values can be incorporated to enhance equity, accessibility, and quality in inclusive education. This study aims to analyze inclusive education management models in Indonesia from an Islamic education perspective and to provide insights for more holistic implementation. The methodology employs qualitative content analysis through in-depth library research, comprising two phases: decontextualization, in which primary and secondary sources are collected and coded, and recontextualization, in which codes are grouped into subthemes and broader categories. Findings indicate strong normative alignment between inclusive education policies and Islamic teachings, which emphasize equality, non-discrimination, and the philosophical obligation to educate. However, gaps persist due to limited awareness and understanding among educators and communities. The study highlights the need for curriculum and learning practices that are accommodating and value-driven, offering implications for policymakers, practitioners, and educational institutions in developing sustainable, equitable, and ethically grounded inclusive education.